How commenters use online forums as spaces for journalism's boundary work. (March 2018) - Wolfgang, J. David
Journalists and online commenters compete for control over news forums. The negotiation of how forums are used, what norms are accepted, and how participants can work together are critical issues for building better forums. This study uses boundary work and a textual analysis of comments to consider how commenters understand best practices and the journalist's role. Commenters express three hierarchical roles for journalists based on differing philosophies of journalist roles and audience autonomy.